The Application of Technological Pedagogical and Content Knowledge (TPACK) to Student Learning Motivation and Learning Outcomes in Physical Education - Joan Rhobi Andrianto; Arnaz Saputro (Journal of Physical Education and Health Science, 2026)
The development of digital technology supports learning innovations that have the potential to improve student motivation and learning outcomes. This study aims to examine the effect of TPACK-based blended learning implementation on Physical Education (PJOK) learning for eleventh-grade students at SMA Negeri 1 Ploso. The method used was an experiment with a control and treatment group, accompanied by a pretest and posttest. The results of the Kruskal-Wallis test showed a significance value > 0.05, but there were differences in the average values. The treatment group had higher learning motivation (52.62) than the control group (48.38), as well as slightly better learning outcomes (8.614 compared to 8.605). Thus, the implementation of TPACK-based blended learning has a positive effect on increasing student motivation and learning outcomes in PJOK learning